Certain lexicography features of the Russian predicative verbs describing the emotion concept - Samedov D.S., Borzova S.V., Gasanova M.A., (Opción, 2019)
The article is devoted to problems of lexicographic derivative verbal lexemes. In work data of three Russian explanatory dictionaries are compared, inaccuracies in the creation of dictionary definitions of the described verbs come to light. As a result, need to include the initial derivative base morpheme in the interpretation of a derivative word is emphasized, the attention to an obligatory reflection of formal and semantic links of related words is paid. In conclusion, such creation of the dictionary entries understanding the value of a derivative that is especially important when studying the verbal lexicon having national and specific character